Sodium ferric phosphate pyrophosphate-based composite material as well as preparation method and application thereof
By generating iron-based phosphide nanoparticles in situ on the surface of sodium ferrous pyrophosphate particles, a heterogeneous interface network is constructed, and the problem of insufficient conductivity of sodium ferrous pyrophosphate materials is solved, and high-rate performance and cyclic stability is improved. It is suitable for high-power sodium ion energy storage devices.
Patent Information
- Application Number
- CN202510885052.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-09-02
AI Technical Summary
The existing sodium ferric pyrophosphate material has low intrinsic electronic conductivity, which limits its practical application performance in high-rate charging and discharging, and the existing improvement methods have problems such as insufficient stability or high cost.
By generating iron-based phosphide nanoparticles in situ on the surface of sodium ferric pyrophosphate particles, forming a tightly bound heterointerface network, building electron and ion dual channels to improve electron conductivity and sodium ion migration efficiency.
It significantly improves the rate performance and cycle stability of the material, reduces electrode polarization, promotes rapid diffusion of sodium ions, inhibits crystal collapse, and achieves high conductivity and structural stability. It is suitable for high-power sodium ion energy storage devices.
Smart Images

Figure CN120573673A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and more specifically, to a sodium iron phosphate pyrophosphate-based composite material, a preparation method thereof, and applications thereof. Background Art
[0002] Sodium ferric pyrophosphate (Na4Fe3(PO4)2(P2O7), NFPP) has attracted widespread attention as a cathode material for sodium-ion batteries due to its abundant elemental resources, excellent structural stability, and environmental friendliness. NFPP has a NASICON structure, which provides three-dimensional ion channels and facilitates rapid sodium ion migration. However, its low intrinsic electronic conductivity limits its practical application in high-rate charge and discharge applications.
[0003] Common methods for improving conductivity include carbon coating and metal doping, but these methods suffer from issues such as insufficient coating stability, difficulty controlling doping, and high costs. In recent years, heterostructure engineering has demonstrated unique advantages in improving electrode reaction kinetics. In particular, constructing metal phosphide interfaces that act as electron channels is considered an effective strategy for enhancing electron migration and interfacial activity.
[0004] However, there are currently no reports of methods for performing controlled atmosphere reduction treatment on the surface of NFPP to in situ form iron-based phosphide nanoparticles, thereby achieving simultaneous improvement in electron channel construction and rate performance. Therefore, there is an urgent need to develop a new NFPP composite material with a rational structure and industrial scalability. Summary of the Invention
[0005] To solve the above technical problems, the present invention proposes a NFPP composite material with an in-situ constructed iron-based phosphide heterogeneous interface on the surface. Through controlled atmosphere reduction treatment, conductive iron-based phosphide nanoparticles are generated in situ on the surface of NFPP particles, forming a tightly bound heterogeneous interface network, thereby realizing dual-channel coordinated transmission of electrons and ions, and significantly improving the rate performance.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] A sodium iron phosphate pyrophosphate-based composite material, the composite material has a core-shell structure, and comprises a matrix material, a heterogeneous interface layer and a coating layer from the inside to the outside. The chemical formula of the matrix material is Na4Fe x (PO4)2P2O7, the heterogeneous interface layer is iron-based phosphide nanoparticles distributed on the surface of the base material, and the coating layer is a carbon layer; the iron-based phosphide includes at least one of FeP and Fe2P; 3≤x≤4.
[0008] In some embodiments, the iron-based phosphide nanoparticles have a particle size of 5-50 nm.
[0009] In some embodiments, the mass fraction of the iron-based phosphide accounts for 0.1-3% of the total mass of the composite material.
[0010] The present invention also provides a method for preparing the sodium iron phosphate pyrophosphate-based composite material of any of the above embodiments, wherein the method uses a carbon-coated sodium iron phosphate pyrophosphate material as a precursor, places the precursor in a reducing atmosphere for heat treatment, and obtains the sodium iron phosphate pyrophosphate-based composite material.
[0011] The present invention firstly treats sodium iron pyrophosphate (Na4Fe x After the main crystal phase of the (PO4)2(P2O7)) / carbon material is constructed, it is placed in a controlled reducing atmosphere for heat treatment, so that some of the iron ions on its surface are reduced and react with the phosphorus source to generate iron-based phosphide (such as FeP, Fe2P) nanoparticles in situ. This process does not require the introduction of exogenous phosphorus or iron, and a stable conductive heterogeneous interface structure can be constructed on the surface of sodium iron pyrophosphate particles. Compared with the traditional single carbon coating method, the precipitated iron-based phosphide has higher electronic conductivity and can significantly improve the surface electron transport efficiency; at the same time, the heterogeneous interface can also promote the rapid diffusion of sodium ions and effectively reduce interface polarization. Furthermore, the interface structure exhibits excellent structural stability during long cycles, which helps to inhibit crystal collapse and activity decay, thereby achieving capacity retention and performance improvement of sodium iron pyrophosphate under high-rate discharge conditions.
[0012] In some embodiments, the particle size of the iron-based phosphide nanoparticles is 5-50 nm, for example, any one of 1 nm, 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm, or a numerical range consisting of any two thereof; in addition, the mass fraction of the iron-based phosphide accounts for 0.1-3% of the total mass of the composite material, including but not limited to any one of 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, and 3%, or a numerical range consisting of any two thereof; the precipitation of iron-based phosphide nanoparticles of a specific particle size can significantly improve the electronic and ionic conductivity and stability of the composite material surface, thereby improving the rate performance and cycle life of the battery.
[0013] In some embodiments, the heat treatment temperature is 400-600°C; specifically, including but not limited to any one or a numerical range consisting of any two of 400°C, 450°C, 500°C, 550°C, and 600°C.
[0014] In some embodiments, the heat treatment time is 0.5-10 h, including but not limited to any one or any two of 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, and 10 h.
[0015] In some embodiments, the reducing atmosphere comprises, by volume, 0-10% reducing gas and 90-100% protective gas; the volume of the reducing gas is greater than 0; preferably, the volume content of the reducing gas is 1-10%, including but not limited to any one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%, or a numerical range consisting of any two of these.
[0016] In some embodiments, the reducing gas is H2 and / or CO; the protective gas includes one of nitrogen, helium, and argon; for example, in the reducing atmosphere, the gas composition by volume ratio includes but is not limited to 4% H2 / 96% N2, 5% H2 / 95% Ar, 10% CO / 90% N2, 4% CO / 96% N2, 2% H2 / 98% N2, etc.
[0017] In some embodiments, the matrix material is sodium ferric pyrophosphate (Na4Fe x The (PO4)2P2O7) material is granular, with a regular spherical or polyhedral morphology, and a particle size distribution of 0.5-5 μm, including but not limited to any one or any two of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.
[0018] In some embodiments, the preparation of the carbon-coated sodium iron phosphate precursor comprises the following steps:
[0019] 1) Weighing a soluble sodium source, an iron source, a phosphorus source, and a carbon source according to stoichiometric amounts and mixing them with water to form a precursor slurry;
[0020] 2) placing the mixed slurry into a spray dryer and spray drying to obtain a precursor powder;
[0021] 3) In an inert atmosphere, the temperature is first raised to 300-400° C. for sintering, and then the temperature is raised to 500-600° C. for secondary sintering to obtain a carbon-coated sodium iron phosphate pyrophosphate material.
[0022] In some embodiments, the sodium source is at least one of sodium dihydrogen phosphate, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium acetate, and sodium citrate.
[0023] In some embodiments, the iron source is at least one of ferroferric oxide, ferric oxide, ferric chloride, ferrous oxalate, ferrous oxalate, ferrous sulfate, and ferrous ammonium sulfate.
[0024] In some embodiments, the phosphorus source is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.
[0025] In some embodiments, the carbon source is at least one of sucrose, soluble starch, cellulose, glucose, and ascorbic acid.
[0026] In some embodiments, in step 3), the inert atmosphere is one of nitrogen atmosphere, argon atmosphere, and helium atmosphere.
[0027] In some embodiments, the molar ratio of the sodium source, the iron source, and the phosphorus source is 3.9-4.2:x:3.9-4.2.
[0028] In some embodiments, the amount of the carbon source added is 0.5-10% of the mass of the sodium source, iron source, phosphorus source and carbon source; including but not limited to 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any two of the numerical range.
[0029] The present invention also provides a positive electrode material, which includes the composite material of any of the above embodiments or the composite material obtained by the preparation method of any of the above embodiments.
[0030] The present invention also provides a positive electrode, which comprises the positive electrode material mentioned above.
[0031] The present invention also provides an electrochemical energy storage device, which includes the above-mentioned positive electrode. Specifically, the electrochemical energy storage device includes a sodium ion battery, a sodium ion capacitor, etc.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The composite material of the present invention realizes the formation of a highly conductive heterogeneous interface by in-situ constructing iron-based phosphide (such as FeP and / or Fe2P) nanoparticles on the surface of the sodium iron phosphate pyrophosphate matrix material, so that the resulting composite material is significantly enhanced in terms of electron and ion transport. On the one hand, the iron-based phosphide has excellent electronic conductivity and can construct a stable electron transmission channel on the surface of the material, reduce electrode polarization, and effectively improve the high-rate performance of the battery; on the other hand, the heterogeneous interface structure can be conducive to charge accumulation, promote the rapid migration of sodium ions, and maintain the stability of the crystal structure during long cycles, thereby suppressing the attenuation of active materials. In addition, the interface is generated in situ, without the need for expensive raw materials, avoiding complex coating processes, and ensuring a simple process with strong controllability.
[0034] Through the structure and process design proposed in the present invention, the obtained composite material is used as an electrode material, and has excellent rate performance, cycle stability and interface conductivity, especially exhibiting excellent rate performance and cycle stability when used under high current density.
[0035] In addition, the composite material preparation process of the present invention is low-cost and scalable, has good industrial application prospects, and can be widely used in high-power sodium ion energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is an SEM image of the sodium iron pyrophosphate matrix material with in-situ surface iron-based phosphide heterogeneous interface prepared in Example 1. DETAILED DESCRIPTION
[0037] The following description sets forth numerous specific details to facilitate a thorough understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art may make similar modifications without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific implementations disclosed below.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] Example 1
[0040] A method for preparing a sodium iron pyrophosphate positive electrode active material with an in-situ surface construction of an iron-based phosphide heterogeneous interface comprises the following steps:
[0041] S1. Add 485 g of sodium dihydrogen phosphate, 450 g of ferrous oxalate dihydrate, 90 g of citric acid, and 18 g of thiourea to 3 L of deionized water, and stir in a ball mill at a speed of 600 rpm for 5 h to obtain a slurry;
[0042] S2. The slurry is transported to a spray dryer through a peristaltic pump. The air inlet temperature is 180°C, the air outlet temperature is 100°C, the air source is compressed air, the nozzle diameter is 2.0 mm, and it is preheated to 150°C before entering the spray gun. The feed rate is 3500 ml / h to obtain dry precursor particles.
[0043] S3. placing the precursor particles in a tube furnace, heating to 400° C. at a rate of 5° C. / min in a nitrogen atmosphere for sintering for 3 h, and then heating to 600° C. at a rate of 5° C. / min for a second sintering for 5 h to obtain a carbon-coated sodium iron phosphate pyrophosphate matrix material;
[0044] S4. Placing the matrix material in a reducing atmosphere and heat treating it at 500° C. for 5 hours to obtain a sodium iron pyrophosphate / carbon positive electrode active material with an iron-based phosphide heterogeneous interface; wherein the reducing atmosphere is composed of 4% H2 and 96% N2 by volume.
[0045] The positive electrode active material obtained in this example was tested by scanning electron microscopy. The test results are as follows: Figure 1 As shown. Figure 1 The positive electrode active material obtained in this embodiment clearly has nano-iron phosphide particles precipitated on the surface of the sodium iron pyrophosphate matrix material.
[0046] The electrochemical performance of the obtained positive electrode active material was tested as follows:
[0047] The positive electrode active material, conductive agent carbon black: binder PVDF were mixed in a mass ratio of 7:2:1. After thorough grinding, an appropriate amount of NMP was added to obtain a uniform slurry. The slurry was coated on an aluminum foil current collector, placed in a vacuum drying oven, dried at 120°C, then taken out and cut into discs. A metallic sodium sheet was used as the counter electrode. 1M NaClO4 / EC:DMC:EMC (1:1:1) was used as the electrolyte. After assembling button cells, the electrochemical performance was tested.
[0048] After testing, the positive electrode active material obtained in this example has a discharge capacity of 95 mAh / g at a voltage of 1.7-4.3 V and a rate of 0.5 C.
[0049] The positive electrode active material obtained in this example has a discharge specific capacity of 91 mAh / g at a voltage of 1.7-4.3 V and a rate of 5 C, and a corresponding capacity retention rate of 95.8%.
[0050] Example 2
[0051] A method for preparing a sodium iron pyrophosphate positive electrode active material with an in-situ surface construction of an iron-based phosphide heterogeneous interface comprises the following steps:
[0052] S1. Add 485 g of sodium dihydrogen phosphate, 450 g of ferrous oxalate dihydrate, 90 g of citric acid, and 18 g of thiourea to 3 L of deionized water, and stir in a ball mill at a speed of 600 rpm for 5 h to obtain a slurry;
[0053] S2. The material is transported to the spray dryer through a peristaltic pump. The air inlet temperature is 180°C, the air outlet temperature is 100°C, the air source is compressed air, the nozzle diameter is 2.0 mm, and it is preheated to 150°C before entering the spray gun. The feed rate is 3500 ml / h to obtain dry precursor particles.
[0054] S3. placing the precursor particles in a tube furnace, heating to 400° C. at a rate of 5° C. / min in a nitrogen atmosphere for sintering for 3 h, and then heating to 600° C. at a rate of 5° C. / min for a second sintering for 5 h to obtain a carbon-coated sodium iron phosphate pyrophosphate matrix material;
[0055] S4. Placing the matrix material in a reducing atmosphere and heat treating it at 500° C. for 10 hours to obtain a sodium iron pyrophosphate / carbon positive electrode active material with an iron-based phosphide heterogeneous interface; wherein the reducing atmosphere is composed of 4% H2 and 96% N2 by volume.
[0056] After testing, the positive electrode active material obtained in this comparative example has a discharge capacity of 91 mAh / g at a voltage of 1.7-4.3 V and a rate of 0.5 C.
[0057] The positive electrode active material obtained in this comparative example has a discharge specific capacity of 83 mAh / g at a voltage of 1.7-4.3 V and a rate of 5 C, and a corresponding capacity retention rate of 91.2%.
[0058] Comparative Example 1
[0059] A method for preparing a positive electrode active material of sodium iron phosphate pyrophosphate without in-situ treatment comprises the following steps:
[0060] S1. Add 485 g of sodium dihydrogen phosphate, 450 g of ferrous oxalate dihydrate, 90 g of citric acid, and 18 g of thiourea to 3 L of deionized water, and stir in a ball mill at a speed of 600 rpm for 5 h to obtain a slurry;
[0061] S2. The slurry is transported to a spray dryer through a peristaltic pump. The air inlet temperature is 180°C, the air outlet temperature is 100°C, the air source is compressed air, the nozzle diameter is 2.0 mm, and it is preheated to 150°C before entering the spray gun. The feed rate is 3500 ml / h to obtain dry precursor particles.
[0062] S3. Place the precursor particles in a tubular furnace, raise the temperature to 400°C at a rate of 5°C / min in a nitrogen atmosphere, and sinter for 3 hours. Then raise the temperature to 600°C at a rate of 5°C / min and sinter for a second time for 5 hours to obtain a carbon-coated sodium iron phosphate pyrophosphate positive electrode active material.
[0063] After testing, the positive electrode active material obtained in this comparative example has a discharge capacity of 83 mAh / g at a voltage of 1.7-4.3 V and a rate of 0.5 C.
[0064] The positive electrode active material obtained in this comparative example has a discharge specific capacity of 62 mAh / g at a voltage of 1.7-4.3 V and a rate of 5 C, and a corresponding capacity retention rate of 74.7%.
[0065] Comparative Example 2
[0066] A method for preparing a sodium iron pyrophosphate positive electrode active material with an in-situ surface construction of an iron-based phosphide heterogeneous interface comprises the following steps:
[0067] S1. Add 485 g of sodium dihydrogen phosphate, 450 g of ferrous oxalate dihydrate, 90 g of citric acid, and 18 g of thiourea to 3 L of deionized water, and stir in a ball mill at a speed of 600 rpm for 5 h to obtain a slurry;
[0068] S2. The slurry is transported to a spray dryer through a peristaltic pump. The air inlet temperature is 180°C, the air outlet temperature is 100°C, the air source is compressed air, the nozzle diameter is 2.0 mm, and it is preheated to 150°C before entering the spray gun. The feed rate is 3500 ml / h to obtain dry precursor particles.
[0069] S3. Place the precursor particles in a tubular furnace, raise the temperature to 400°C at a rate of 5°C / min in a nitrogen atmosphere, and sinter for 3 hours. Then raise the temperature to 600°C at a rate of 5°C / min and sinter for a second time for 5 hours to obtain a carbon-coated sodium iron phosphate pyrophosphate matrix material.
[0070] S4. Placing the matrix material in a reducing atmosphere and heat treating it at 300° C. for 5 hours to obtain a sodium iron pyrophosphate / carbon positive electrode active material with an iron-based phosphide heterogeneous interface; wherein the reducing atmosphere is composed of 4% H2 and 96% N2 by volume.
[0071] After testing, the positive electrode active material obtained in this example has a discharge capacity of 85 mAh / g at a voltage of 1.7-4.3 V and a rate of 0.5 C.
[0072] The positive electrode active material obtained in this example has a discharge specific capacity of 70 mAh / g at a voltage of 1.7-4.3 V and a rate of 5 C, and a corresponding capacity retention rate of 82.4%.
[0073] The electrochemical performance test results of the positive electrode active materials obtained in Example 1-2 and Comparative Example 1-2 are shown in Table 1.
[0074] Table 1 Electrochemical performance test results of positive electrode active materials of Examples 1-2 and Comparative Examples 1-2
[0075]
[0076] The present invention can effectively improve the specific capacity of the sodium iron pyrophosphate material at high rate by in-situ construction of a specific iron-based phosphide heterogeneous interface on the surface of the base material, thereby improving the rate performance of the material.
[0077] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A sodium iron phosphate pyrophosphate-based composite material, characterized in that: The composite material has a core-shell structure, and includes a matrix material, a heterogeneous interface layer and a coating layer from the inside to the outside. The chemical formula of the matrix material is Na4Fe x (PO4)2P2O7, the heterogeneous interface layer is iron-based phosphide nanoparticles distributed on the surface of the base material, and the coating layer is a carbon layer; the iron-based phosphide includes at least one of FeP and Fe2P; 3≤x≤4.
2. The sodium iron phosphate pyrophosphate based composite material according to claim 1, characterized in that The particle size of the iron-based phosphide nanoparticles is 5-50 nm.
3. The sodium iron phosphate pyrophosphate based composite material according to claim 1, characterized in that The mass fraction of the iron-based phosphide accounts for 0.1-3% of the total mass of the composite material.
4. The method for preparing the sodium iron phosphate pyrophosphate-based composite material according to any one of claims 1 to 3, characterized in that: A carbon-coated sodium iron phosphate pyrophosphate material is used as a precursor, and the precursor is placed in a reducing atmosphere for heat treatment to obtain the sodium iron phosphate pyrophosphate-based composite material.
5. The method for preparing the sodium iron phosphate pyrophosphate based composite material according to claim 4, wherein: The heat treatment temperature is 400-600° C.; and / or the heat treatment time is 0.5-10 h.
6. The method for preparing the sodium iron phosphate pyrophosphate based composite material according to claim 4, wherein: The reducing atmosphere comprises, by volume, 0-10% reducing gas and 90-100% protective gas; the volume of the reducing gas is greater than 0.
7. The method for preparing the sodium iron phosphate pyrophosphate based composite material according to claim 6, wherein: The reducing gas is H2 and / or CO; the protective gas includes one of nitrogen, helium and argon.
8. A positive electrode material, characterized in that The composite material comprises the composite material according to any one of claims 1 to 3.
9. A positive electrode, characterized in that Comprising the positive electrode material according to claim 8.
10. An electrochemical energy storage device, characterized in that: Comprising the positive electrode according to claim 9.
Citation Information
Cited By
Secondary battery, battery device, and electric device
CN120727938A
Modified graphene coated ferric sodium pyrophosphate, preparation method and sodium ion battery
CN121546020A
